Evaluation of the objective adjustment method of the continental seamer at the Yara Productive Factory (Original) (REDEL. Revista Granmense de Desarrollo Local, 2023)
In Yara Productive Factory, which belongs to the Unidad Empresarial de Base Conservas de Vegetales de Granma, there is a ½ kg tinplate container sealing machine that closes different products, both for domestic consumption and for tourism. Among the main objectives established to determine the quality in the manufacturing processes of the products is related to the evaluation and analysis of the parameters of the sealing or double sealing, which must comply with the standards established for this process. Due to the great variety of container formats that exist and their different characteristics, the breakages that occur and the replacement of some of their components, it is necessary to make constant adjustments in the sealing machines that define the quality and acceptability of the closure. These adjustments require great precision, time and the use of some resources in the process, in order to guarantee the tightness of the package and the preservation of the packaged and capped products. The objective of this article is to evaluate the effectiveness of the target adjustment method in the optimal adjustment of the Continental seamer for ½ kg containers, in order to obtain a closure with the recommended specifications according to the standards, using a minimum of time and resources. Theoretical methods (analysis-synthesis, induction-deduction), empirical methods (documentary analysis, experiment) and mathematical statistics for data processing were used for the development of this research.
Keywords: container seamers; tinplate; target setting; canning; rolls; double sealing